Chlorogenic Acid Ameliorates Colitis and Alters Colonic Microbiota in a Mouse Model of Dextran Sulfate Sodium-Induced Colitis - Zhang, Peng; Jiao, Huanli; Wang, Chunli; Lin, Yuanbang; You, Shengyi (Frontiers in Physiology, 2019)
This study evaluated the mitigating effects of dietary chlorogenic acid (CGA) on colon damage and the bacterial profile in a mouse model of dextran sulphate sodium (DSS)-induced colitis. C57BL/6J mice were randomly assigned to receive one of the following treatments: (i) basal diet; (ii) basal diet with 2% CGA; (iii) basal diet with 2.5% DSS or (iv) basal diet with 2% CGA and 2.5% DSS. Following a 2-week pre-treatment period, mice in the DSS and CGA-DSS groups received 2.5% DSS in drinking water for 5 days, while the other two groups received sterile water. Compared to DSS alone, CGA was found to reduce the disease activity index, myeloperoxidase activity and tumour necrosis factor-α levels in colon tissues (P < 0.05). CGA also ameliorated DSS-induced inflammatory responses, reduced colon shortening and decreased the histological scores (P < 0.05). In an evaluation of the relative abundances of bacteria in the faecal microbiota, we found that CGA reversed the decrease in diversity caused by DSS and improved the relative abundance of organisms in the genus Lactobacillus (P < 0.05). These results indicate that CGA maintains intestinal health and reduces DSS-induced colon injury by decreasing the production of pro-inflammatory cytokines and restoring intestinal microbial diversity.